2011
DOI: 10.1007/s00540-011-1210-8
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury during aortic arch surgery under deep hypothermic circulatory arrest

Abstract: A high incidence of AKI during AAS under DHCA was confirmed. Because AKI is highly associated with aortic surgery, novel approaches for protecting the kidneys other than deep hypothermia are needed. The logistic regression model identified HT, emergency surgery, and duration of DHCA as independent risk factors for AKI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…The logistic regression model identified DHCA time >30 minutes as an independent risk factor for AKI, which was consistent with a previous study. 24 Meanwhile, in a previous study reported by Englberger et al, 3 the use of DHCA was not an independent risk factor. This study did not exclude the influence of patient demographics from the multivariate analysis, and provided increased age, elevated BMI and a history of hypertension as independent risk factors.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The logistic regression model identified DHCA time >30 minutes as an independent risk factor for AKI, which was consistent with a previous study. 24 Meanwhile, in a previous study reported by Englberger et al, 3 the use of DHCA was not an independent risk factor. This study did not exclude the influence of patient demographics from the multivariate analysis, and provided increased age, elevated BMI and a history of hypertension as independent risk factors.…”
Section: Discussionmentioning
confidence: 81%
“…Demographic variables previously reported as risk factors for AKI were included such as age, 3 , 6 , 7 gender 7 and BMI. 3 A past medical history of hypertension, 2 , 3 , 24 diabetes mellitus, 7 , 9 , 10 smoking history, 9 and cerebrovascular accident 11 have also been reported as predictors for AKI and were included here. However, these factors could function as confounders of attempts to find independent risk factors for AKI, and their clinical significance is limited as these are not modifiable.…”
Section: Discussionmentioning
confidence: 99%
“…ARF = acute renal failure; HCA = hypothermic circulatory arrest. more protective towards the visceral organs and kidneys, new clinical trends advocate moderate hypothermia without compromise in renal function [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In multivariable models, estimates were adjusted for the following risk factors for AKI following cardiac or thoracic aortic surgery: age, sex, body mass index, baseline estimated glomerular filtration rate, hypertension, diabetes mellitus, CHF, CPB duration, use of DHCA, ejection fraction, preoperative hemoglobin, and aprotinin exposure (1-3, 7, 18). Concomitant CABG was further included in the model as a surrogate for coronary artery disease and because patients undergoing CABG surgery have been shown to be at higher risk of AKI with short interval catheterization (6-9, 11).…”
Section: Methodsmentioning
confidence: 99%